"By degrees it grows still more refin'd" : Katherine Philips' curating of the Tutin manuscript. Issue 3 (4th May 2022) - Trolander, Paul
ABSTRACT: Early-modern Anglo-Welsh poet, Katherine Philips (self-styled "Orinda") often described as a social author and manuscript poet, maintained a selected copy of her poems in what is now known as the Tutin Ms. (NLW MS 775B). She likely used Tutin to cultivate social and literary capital among the coterie groups she interacted with during the 1650s, both in London and in Wales. This essay argues that Philips actively curated Tutin from 1655 through 1658 in order to appeal to changing coterie reactions to her verses and to accommodate newer work. Philips initially appears to have planned Tutin as a manuscript edition of her poems, and there is physical evidence in the volume that she may have conceived of her notebook as a manuscript book. Philips experimented with graphical elements (page numbering, lined margins, catch-words), as well as physically separated her poems into two major groupings, social-network and public-sphere poems. Such experiments were likely attempts to advance her reputation as a poet of public stature, to suppress earlier sexually sensitive work, and to compile what she regarded as a repository of author-approved literary capital. However, limitations that Tutin's physical division imposed on the placement of poems, difficulties in correcting errors in copying, mutilations from the removal of politically sensitive contents, and haphazard insertion of new verse after 1658, contributed to Philips abandoning Tutin as a show-case of her poems. The Restoration provided Philips an impetus to curate a new set that could appeal to Restoration Royals and royalists, and she took this opportunity to revise and edit, insert older verse once suppressed, suppress some verses Tutin had contained, and add newer poems drafted 1660–62. This newly crafted repository of author-approved literary capital, referred to throughout the essay as KP1, though now lost, is evidenced by collation of the variant readings in the main contemporary witnesses, including the manuscripts Tutin Ms., Dering Ms. (HRC 151), Clarke miscellany (WC MS 58), Rosania Ms. (NLW MS 776B), as well as the print editions of 1664 and 1667.